2017
DOI: 10.4103/jomfp.jomfp_214_16
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis: A quantitative assessment of serum malondialdehyde, superoxide dismutase and correlation with clinical staging

Abstract: Background:Oral submucous fibrosis (OSMF) is a progressive disorder affecting the oral mucosa. OSMF predominantly seen in South-east Asian countries. There are some biochemicals parameters which are modify in oral submucous fibrosis; this alteration can be used as a tool for diseases progress and avert malignant transformation.Aims and Objectives:The aim of this study is to evaluate the serum malondialdehyde (malondialdehyde [MDA]), and Superoxide dismutase (SOD) in oral sub mucous fibrosis cases and compare c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Another study with similar results was conducted by Gurudath et al [16], where the mean serum SOD level in OSF group was significantly decreased as compared to the control group. Also, the study conducted by Bale R. et al [17] showed consistent results. Comparison of SOD levels between healthy volunteers and OSMF participants was statistically significant.…”
Section: Resultssupporting
confidence: 58%
“…Another study with similar results was conducted by Gurudath et al [16], where the mean serum SOD level in OSF group was significantly decreased as compared to the control group. Also, the study conducted by Bale R. et al [17] showed consistent results. Comparison of SOD levels between healthy volunteers and OSMF participants was statistically significant.…”
Section: Resultssupporting
confidence: 58%
“…Serum samples from OSMF patients revealed increased MDA [24], ceruloplasmin [29], LPOs [8], nitric oxide [30], and decreased levels of beta-carotene, vitamin E [8], and SOD levels [30]. Human studies largely demonstrated elevated levels of oxidative stress biomarkers serum MDA [8,23,25,26,83], salivary 8-hydroxy-2 -deoxyguanosine [31], salivary 8isoprostane [33], salivary lactoperoxidase and total salivary protein [34], and serum copper [27,28], calcium, magnesium, potassium, iron, LPOs, conjugated dienes, and hydroxyl radicals [28]. MDA was found by two articles to be more significant with higher clinical OSMF staging and grading [8,83], while 8-OHdG (salivary oxidative stress biomarker) levels were almost double in OSMF patients [31].…”
Section: Oxidative Stress Biomarkers Is Osmfmentioning
confidence: 99%
“…Human studies largely demonstrated elevated levels of oxidative stress biomarkers serum MDA [8,23,25,26,83], salivary 8-hydroxy-2 -deoxyguanosine [31], salivary 8isoprostane [33], salivary lactoperoxidase and total salivary protein [34], and serum copper [27,28], calcium, magnesium, potassium, iron, LPOs, conjugated dienes, and hydroxyl radicals [28]. MDA was found by two articles to be more significant with higher clinical OSMF staging and grading [8,83], while 8-OHdG (salivary oxidative stress biomarker) levels were almost double in OSMF patients [31]. Interestingly, studies investigating the level of antioxidant enzymes in OSMF have produced conflicting results.…”
Section: Oxidative Stress Biomarkers Is Osmfmentioning
confidence: 99%
“…The included studies had found a statistically significant increase in serum MDA levels in OSMF patients compared with controls (p < 0.001). 1,18,20,22,26,28,29,30,31,32,33,34,35,36,37,38 Similarly, other studies also observed a significant difference p-value <0.01 4 and p-value <0.05. 39,40 A few studies have also reported significantly higher salivary MDA levels in OSMF compared with healthy subjects (p < 0.001).…”
Section: Discussionmentioning
confidence: 73%